Bericht über Forschungsaufenthalte an der Universität Kyoto - Dillmann, Meiko; Koziol, Gabriele (Zeitschrift für Japanisches Recht, 2010)
In 2008 and 2009 we spent several months as guest researchers at Kyoto University, supported by scholarships from the German Academic Exchange Service and the Japan Foundation, respectively. In the outstanding research environment of Kyoto University and under the excellent supervision and guidance of Prof. Keizô Yamamoto we carried out research for our respective doctoral theses on the protection of privacy against media invasions under German and Japanese law (M. Dillmann) and on security interests in intellectual property licences under German, Austrian and Japanese law (G. Koziol). We were warmly welcomed into the academic community of Kyoto University and beyond which helped to further our knowledge of Japanese law on a broader scale and offered many pleasant encounters on a personal level.